Development of a low-cost efficient wireless intelligent sensor for strain measurements (LEWIS-S). (4th June 2021) - Robbins, Eric; Cobo, Nicolas; Diaz, Jorshua; Moreu, Fernando
Abstract: Generally, measuring strain can be a very difficult and expensive task due to the complex demands of data acquisition (DAQ) systems and pasting strain gauges (SGs) which can disincentivize taking strain measurements overall. However, measuring strain can quantify stresses and mechanical properties which can aid in determining safe operating conditions for materials. The purpose of this research is to introduce an alternative resource to efficiently and accurately measure strain in a cost-effective and easy-to-use platform. In order to accomplish this goal, a new low-cost efficient wireless intelligent sensor for strain (LEWIS-S) was developed and experimentally tested. The LEWIS-S functions on a platform of various Arduino hardware components and free integrated development environment software. The sensor is approximately 95% cheaper than standard commercial equipment and the compact design reduces the footprint of the equipment by approximately 75%. Additionally, the LEWIS-S has an inherently simple design such that limited knowledge is required to manually assemble and use the sensor. Furthermore, the versatility of the sensor allows for the compatibility of different SG attachments which can be useful for sensing optimization during testing. As such, a uniaxial friction-magnetic strain checker and a traditional pasted uniaxial SG were used in the validation testing in this research. Static and dynamic validation tests were conducted on a small cantilever beam where the LEWIS-S was compared to a commercial DAQ system to verify the accuracy and dependability of the sensor. Results from the experimental testing demonstrated good agreement between the LEWIS-S and commercial equipment.